Differences between brain responses to peroneal electrical transcutaneous neuromodulation and transcutaneous tibial nerve stimulation, two treatments for overactive bladder - Krhut, Jan; Tintěra, Jaroslav; Rejchrt, Michal; Skugarevská, Barbora; Zachoval, Roman; Zvara, Peter; Blok, Bertil F M (Neurourology and urodynamics, 2023)
OBJECTIVES: To compare brain responses to peroneal electrical transcutaneous neuromodulation (peroneal eTNM®) and transcutaneous tibial nerve stimulation (TTNS), two methods for treating overactive bladder (OAB), using functional magnetic resonance imaging (fMRI). The present study was not designed to compare their clinical efficacy. MATERIALS AND METHODS: This study included 32 healthy adult female volunteers (average age 38.3 years (range 22-73)). Brain MRI using 3 T scanner was performed during three 8-min blocks of alternating sequences. During each 8-min block, the protocol alternated between sham stimulation (30 s) and rest (30 s) for 8 repeats; then peroneal eTNM® stimulation (30 s) and rest (30 s) for 8 repeats; then, TTNS stimulation (30 s) and rest (30 s) for 8 repeats. Statistical analysis was performed at the individual level with a threshold of p = 0.05, family-wise error (FWE)-corrected. The resulting individual statistical maps were analyzed in group statistics using a one-sample t-test, p = 0.05 threshold, false discovery rate (FDR)-corrected. RESULTS: During peroneal eTNM®, TTNS, and sham stimulations, we recorded activation in the brainstem, bilateral posterior insula, bilateral precentral gyrus, bilateral postcentral gyrus, left transverse temporal gyrus, and right supramarginal gyrus. During both peroneal eTNM® and TTNS stimulations, but not sham stimulations, we recorded activation in the left cerebellum, right transverse temporal gyrus, right middle frontal gyrus, and right inferior frontal gyrus. Exclusively during peroneal eTNM® stimulation, we observed activation in the right cerebellum, right thalamus, bilateral basal ganglia, bilateral cingulate gyrus, right anterior insula, right central operculum, bilateral supplementary motor cortex, bilateral superior temporal gyrus, and left inferior frontal gyrus. CONCLUSIONS: Peroneal eTNM®, but not TTNS, induces the activation of brain structures that were previously implicated in neural control of the of bladder filling and play an important role in the ability to cope with urgency. The therapeutic effect of peroneal eTNM® could be exerted, at least in part, at the supraspinal level of neural control.
Keywords: Young Adult; močový měchýř; Transcutaneous Electric Nerve Stimulation; magnetická rezonanční tomografie; mladý dospělý; Urinary Bladder; Brain; Adult; transkutánní elektrická neurostimulace; Tibial Nerve; Aged; dospělí; senioři; hyperaktivní močový měchýř; nervus tibialis; lidé; ženské pohlaví; Humans; Urinary Bladder, Overactive; mozek; Magnetic Resonance Imaging; Female; lidé středního věku; Middle Aged